Oxygen‐Rich Non‐Graphitic Carbon Derived from Citrus sinensis for High‐Energy Density Pseudocapacitive Charge Storage. Issue 47 (17th December 2020) - Tiwari, Bhumika; Joshi, Akanksha; Mohan, Priyank; Kishore Sharma, Raj; Singh, Gurmeet
Abstract: Non‐graphitic carbon is a potential supercapacitor electrode material attributed to the combination of dense porous structure and high surface area. However, production cost limits its high usage. Herein, inexpensive and sustainable flavonoids rich precursor Citrus sinensis is utilized for synthesis of non‐graphitic carbon and is characterised using XRD, Raman, XPS & BET. For controlled porosity, KOH activation at two different temperatures (750 °C & 900 °C) is carried out that result in controlled meso/macro porous carbon with 900 °C activation (AC‐900). The edges of pores with dangling oxygen functionalities (37 %) contributes to pseudocapacitive charge (385.91 F g −1 ) whereas meso/macro pore size distribution facilitates fast diffusion (0.78 × 10 −9  cm 2  s −1 ) in symmetric cell (AC‐900||AC‐900). Furthermore, an impressively high energy density (51.1 Wh kg −1 @ 0.75 A g −1 ) is obtained owing to this blend of controlled porous structure and oxygen functionalities. In future, this study will pave a path for designing of low cost non‐graphitic controlled porous structure carbon. Abstract : Carbon derived from flavonoids rich natural precursors is a cost‐effective route in synthesis of non‐graphitic oxygen rich porous carbon. The combination of electric double layer capacitance and Faradaic pseudocapacitance resulted AC‐900||AC‐900 to deliver an impressively high specific capacitance of 385.91 F g −1, high energy density of 51.1 Wh kg −1 @ 365.87 W kg −1 (0.75 A g −1 in 1 M H2 SO4 ). These promising results presented the applicability of Citrus Sinensis peel derived carbon material as a remarkable step towards sustainable development.